Multiple Somatic Symptoms Linked to Positive Screen for Depression in Pediatric Patients With Chronic Abdominal Pain - Little, Cheryl A. (2007)
OBJECTIVES: Abdominal pain is a frequent childhood complaint, comprising 2% to 4% of all reasons for pediatric office visits. Patients referred for evaluation of chronic abdominal pain (CAP) frequently present with comorbid nonspecific somatic symptoms that may complicate the medical evaluation and lead to unnecessary diagnostic tests and procedures. We tested the hypothesis that multiple nongastrointestinal (GI) symptoms in children presenting with CAP is a marker for clinically significant levels of depressive symptoms. METHODS: Participants were 400 consecutive new patients (ages 8–17 years; 63% female) referred to the pediatric gastroenterology clinic for evaluation of abdominal pain of >3 months’ duration. Patients reported how frequently they experienced 7 non-GI symptoms. Patients were screened for depression with the Children’s Depression Inventory. RESULTS: On the basis of their Children’s Depression Inventory scores, 58 (15%) patients had a positive screen for clinically significant depressive symptoms. Patients with a positive versus negative depression screen did not differ by sex, pain duration or laboratory evidence of organic disease. Patient report of ≥3 non-GI symptoms maximized sensitivity (71%) and specificity (75%) in prediction of depression screening results. With each addition of a non-GI symptom, the odds of a positive screen for depression doubled. CONCLUSIONS: For patients with and without organic disease findings associated with CAP, the presence of ≥3 non-GI symptoms should signal the practitioner to evaluate for depression and may be used as an indicator of the likelihood of depression in the absence of specific inquiry into emotional symptoms.